Influence of radial anatomy on pain experienced during transradial coronary angiography. (1st September 2016) - Hensey, Mark; Cronin, Edel; Owens, Patrick
Abstract: Background: The transradial route has become the primary approach for coronary angiography with the presence of radial artery anomalies found to be 10–20%. There has been limited study on the influence of these anomalies on procedural pain. Our aims were to determine local prevalence of the high radial origin (HRO) anatomical variant; to investigate factors influencing transradial procedural pain; and to determine if HRO specifically was associated with increased pain. Methods: Radial artery anatomy was characterized by arteriography in sequential patients undergoing angiography. Patients were asked to mark their perceived procedural pain on a visual analog scale, which was converted to a pain score. Results: 382 patients were enrolled, 5 were excluded. There were 259 males (68.7%) and 118 females (31.3%). HRO was present in 51 patients (13.5%). Overall mean pain score was 2.6 (SD 2.5). HRO was associated with a higher mean pain score than normal anatomy (3.3 (SD 2.9) vs. 2.4 (SD 2.4) p = 0.027). HRO was not associated with increased procedural failure, screening time or procedure time. When pain score was dichotomized into mild pain (< 4.0) and moderate-to-severe pain (≥ 4.0), HRO was associated with almost double the frequency of moderate-to-severe pain (37.2% vs. 21.1%, p = 0.012). Using a logistic regression model, only female gender, younger age and HRO remained significant predictors of moderate-to-severe pain. Conclusions: There was significantly increased pain in patients with HRO without increased procedure/screening time or procedural failure. Female gender and younger age were also found to be significant predictors of increased pain.